Strategic investment in climate friendly technologies: the impact of permit trade - Mads Greaker; Cathrine Hagem (Statistics Norway, Research Department, 2010)
Our point of departure is that a group of developed countries invest in the development of greenhouse gas (GHG) abatement technologies both at home and in developing countries. Such investments reduce the cost of future GHG abatement, and influence the future GHG abatement choices of both developed and developing countries. We show how a common permit market affects the industrialized countries' strategic investment decisions. As opposed to a situation without a permit market, the industrialized countries may want to overinvest in new GHG abatement technologies both at home and abroad. That is, they increase their R&D investment to such an extent that the cost reductions from the least profitable project actually fall short of the R&D costs. Earlier research has only pointed to overinvestment abroad. Moreover, the effects of investment abroad may be tougher emission reduction targets at home, which is not possible without permit trade.
Keywords: D62; H41; O38; Q58; 330; greenhouse gas abatement technologies; climate policy; strategic investments; permit trade.